Recovery modeling in MPLS networks - Al-Khateeb, Wajdi Fawzi Mohammed; Al-Irhayim, Sufyan; Al-Khateeb, Khalid A. Saeed (2006)
Transmission of QoS based traffic over packet switched network typically requires resource reservation or differentiated treatment to guarantee an acceptable level of performance. But it is also essential to bound the disruption caused by failure of nodes or links for a real time traffic to a limit that is acceptable by the application. In this paper, a simulation platform models the impact of the MPLS recovery/protection schemes on the QoS traffic parameters including disruption time and number of out of order packets arriving at the destination. The simulation considers measures to alleviate drawbacks caused by recovery process.